2020
DOI: 10.3389/fpsyt.2020.581113
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and COVID-19: Can we Predict the Impact of the Pandemic on Alcohol Use Based on the Previous Crises in the 21st Century? A Brief Review

Abstract: The enormous health and economic challenges precipitated by the 2019 coronavirus disease (COVID-19) pandemic are comparable or even greater than those associated with previous historical world crises. Alcohol use, especially drinking to cope with stress, is a concern, as an increase in its sales has been reported in some countries during the quarantine. This study aims to provide a better understanding of what to expect in terms of alcohol consumption, risk factors for excessive use, and its potential conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 66 publications
4
79
1
2
Order By: Relevance
“…Isolated and quarantined people frequently turn to substances (e.g., alcohol consumption) or rewarded behaviors (e.g., online gaming) to cope with their negative feelings (5,6). Previous studies have reported that the impact of disasters, such as traumatic events (i.e., terrorism as 9/11), epidemic outbreaks (i.e., severe acute respiratory syndrome [SARS] in 2003), economic crises (2008's Great Recession), have resulted in increased rates of addictive behaviors, including alcohol drinking and problematic Internet use (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated and quarantined people frequently turn to substances (e.g., alcohol consumption) or rewarded behaviors (e.g., online gaming) to cope with their negative feelings (5,6). Previous studies have reported that the impact of disasters, such as traumatic events (i.e., terrorism as 9/11), epidemic outbreaks (i.e., severe acute respiratory syndrome [SARS] in 2003), economic crises (2008's Great Recession), have resulted in increased rates of addictive behaviors, including alcohol drinking and problematic Internet use (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Exposing children more frequently to parental alcohol consumption may endorse lower risk perception of negative consequences (36) and positive expectations surrounding alcohol use (37) and may also promote a more accessible environment that may facilitate their teenage children's initiation to drinking (38). At the beginning of the COVID-19 pandemic, it was not clear which direction alcohol consumption would take and two hypotheses were raised based on a literature review of previous public health emergencies: a possible increase due to stress, and a possible reduction due to lack of access (3,13). Findings from the present study point to the negative association between HED and those who reported being in quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic, it was not clear which direction alcohol consumption would take and two hypotheses were raised based on a literature review of previous public health emergencies: a possible increase due to stress, and a possible reduction due to lack of access ( 3 , 13 ). Findings from the present study point to the negative association between HED and those who reported being in quarantine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported a high rate of problematic alcohol use as a response to stress and as a coping mechanism following a major life event. [22][23][24][25] For example, almost 25% of New York residents reported increased alcohol use following the attack on the World Trade Center in 2001. 26 A link between anxiety and depressive symptoms and an increase in harmful alcohol use has been documented previously.…”
Section: Discussionmentioning
confidence: 99%